ISLAMIC MODERN RETAIL ATTRIBUTES FOR MUSLIM CONSUMERS PATRONAGE INTENTION - Jatiningrum, Wandhansari Sekar; Astuti, Fatma Hermining; Mastrisiswadi, Hasan (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2021)
Muslim dominates the total population in Indonesia. Islamic modern retail growth in Indonesia is predicted to increase since Muslims started to consider the religion aspects for their daily life. Nevertheless, there has not been much research on this matter. This study aims to investigate Islamic modern retail attributes for Muslim shoppers in Indonesia. Furthermore, this research will focus on the patronage intention of Muslim shoppers. A sample of 144 consumers of modern Islamic retail in Indonesia was collected. The data were collected through a questionnaire and analyzed using multiple linear regression. The results revealed that Islamic modern retail attributes, such as the Islamic store atmosphere and Islamic value, had a significant positive effect on Muslim shopperâ€™s patronage intention. While other attributes, such as Muslim product, humanistic, and halal product certification, have no significant effect on Muslim shopperâ€™s patronage intention. This study conï¬rmed that each one-unit increase in independent variables, namely Muslim product, Islamic store atmosphere, humanistic, halal product certification, and Islamic value, respectively, will cause an increase in patronage intentions of 0.114, 0.238, 0.025, 0.044, and 0.263 unit.